Living Qur'an di Ruang Publik: Makna Sosial Praktik Pengamen Al-Qur'an di Pekanbaru Perspektif Emile Durkheim dan Karl Mannheim - Rinaldo Rinaldo (Insight: Indonesian Journal of Social, Humanity, and Education, 2026)
The phenomenon of Qur'anic buskers in Pekanbaru represents a distinctive form of Living Qur'an that differs from conventional religious practices. Although studies on the Living Qur'an have expanded considerably, limited research has examined this practice as an intersection of religious piety, survival strategies, and the social construction of meaning. This study aims to analyze the practice of Qur'anic busking in Pekanbaru through the sociological perspectives of Emile Durkheim and Karl Mannheim to explain the transformation of the Qur'an's function and social meaning in the public sphere. This research employed a qualitative approach using a descriptive-analytical method. Data were collected through observation, in-depth interviews with Qur'anic buskers and community members, and documentation, and were analyzed using Durkheim's theory of social facts and Mannheim's concepts of objective, expressive, and documentary meaning. The findings indicate that Qur'anic busking is no longer merely an expression of individual piety but has evolved into a survival strategy in response to economic pressures. From Durkheim's perspective, the practice reflects the transformation of the Qur'an's sacred function into a socially recognized practice legitimized through public acceptance. From Mannheim's perspective, the practice embodies objective meaning as an economic activity, expressive meaning as a manifestation of personal religiosity and lived experience, and documentary meaning as a reflection of the relationship between religion, culture, and socio-economic conditions. This study contributes to the Living Qur'an literature by demonstrating that the reception of the Qur'an extends beyond religious devotion to function as a mechanism of social adaptation within contemporary urban society. [Fenomena pengamen Al-Qur'an di Kota Pekanbaru menghadirkan bentuk resepsi Al-Qur'an yang berbeda dari praktik keagamaan konvensional. Meskipun kajian mengenai Living Qur'an terus berkembang, penelitian yang menjelaskan praktik ini sebagai pertemuan antara ekspresi kesalehan, strategi bertahan hidup, dan konstruksi makna sosial masih sangat terbatas. Penelitian ini bertujuan menganalisis praktik pengamen Al-Qur'an di Pekanbaru melalui perspektif sosiologi Emile Durkheim dan sosiologi pengetahuan Karl Mannheim untuk menjelaskan perubahan fungsi serta makna sosial Al-Qur'an dalam ruang publik. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif-analitis. Data diperoleh melalui observasi, wawancara mendalam terhadap pengamen Al-Qur'an dan masyarakat, serta dokumentasi, kemudian dianalisis menggunakan teori fakta sosial Durkheim dan teori makna objektif, ekspresif, dan dokumenter Mannheim. Hasil penelitian menunjukkan bahwa praktik pengamen Al-Qur'an tidak lagi sekadar merepresentasikan kesalehan individual, tetapi juga menjadi strategi bertahan hidup dalam menghadapi tekanan ekonomi. Dalam perspektif Durkheim, praktik tersebut merefleksikan transformasi fungsi sakral Al-Qur'an menjadi praktik sosial yang memperoleh legitimasi melalui penerimaan masyarakat. Sementara itu, perspektif Mannheim menunjukkan bahwa tindakan para pengamen mengandung makna objektif sebagai aktivitas ekonomi, makna ekspresif sebagai representasi pengalaman hidup dan religiositas, serta makna dokumenter yang mencerminkan relasi antara agama, budaya, dan kondisi sosial-ekonomi. Penelitian ini berkontribusi memperluas kajian Living Qur'an dengan menunjukkan bahwa resepsi Al-Qur'an tidak hanya berfungsi sebagai ekspresi keagamaan, tetapi juga sebagai mekanisme adaptasi sosial dalam kehidupan masyarakat urban.]